Chemodivergent reaction of azomethine imines and 2H-azirines for the synthesis of nitrogen-containing scaffolds - Wu, Yufeng; Tian, Bing; Hu, Chao; Sekine, Kohei; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organic & biomolecular chemistry, 2019)
Metal-free reactions of 2-H-azirines with C-, N-cyclic azomethine imines were investigated. The metal-free reactions of 2-H-azirines with C-, N-cyclic azomethine imines were investigated. N-Bridged strained ring-fused triazole derivatives or 1,2,4-triazine derivatives are obtained, and the chemoselectivity is dependent on the protecting group on the azomethine dipole. Although benzoyl-protected starting materials give access to strained polycyclic compounds, a ring-opening occurs in the case of a tosyl protecting group that is cleaved during the process with elimination of sulfinic acid. 1,2,4-Triazine can be prepared on a mmol-scale and concomitantly oxidized with air as an oxidant to form the corresponding ketone, which is an interesting structural motif that can be found in bioactive scaffolds.
Gesehen am 21.10.2019